Penggunaan Proyeksi Iklim untuk Optimalisasi Tata Tanam dengan Kc Berbeda (Studi Kasus : Tanaman Jagung di Satu Titik Tertentu di Jawa Timur) - Amalia, Aqila; Herlina, Ninuk; Kurniawan, Andang (Buletin GAW Bariri (BGB), 2025)
Planting plans in East Java have not yet incorporated climate information. Maize cropping plan is affected by climate change. Many studies related to climate and agriculture still rely on a constant crop coefficient (Kc). This research aims to provide an overview of the use of climate projections in planting plans by employing two different Kc approaches (constant and variative). The 8.5 emission scenarios, subsequently used as inputs in RegCM4 and CSIROMk3.6, used as input of climate change information. Historical interpolated rainfall observation data from 1991 – 2020 (official operational data) is utilized to correct projected rainfall. Projected maximum, average, and minimum temperature data are used to calculate evapotranspiration, which is then refined using in – situ openpan evaporimeter data. Soil water availability is calculated based on parameters outlined in the FAO56 document. Irrigation requirement data is derived from the difference between water availability and the target, determined by the depletion factor using two distinct Kc approaches. The results illustrate how climate projection information, corrected with in-situ data, can be applied to future planning (2021 – 2050 and 2051 – 2080). Consistent with the theory, water availability is expected to decrease, potential harvests to decline, and irrigation needs to rise. This study provides quantitative data that can be further utilized. Future research should consider that employing constant Kc may lead to significant discrepancies in water requirement calculations, contrast with the fact that each plant growth phase has different Kc.